1985
DOI: 10.1042/cs0690321
|View full text |Cite
|
Sign up to set email alerts
|

Increased albumin and normal dextran clearances in protein-overload proteinuria in the rat

Abstract: Female Wistar rats were made heavily proteinuric by daily intraperitoneal injections of bovine serum albumin over 5 days. The size and charge permeability characteristics of the glomerular filter in this condition were determined by studying the renal handling of poly-dispersed uncharged dextran over the range of molecular radii 2-6 nm (albumin 3.6 nm), and of endogenous rat serum albumin over the same clearance period. In proteinuric rats the clearance of rat serum albumin was significantly increased with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
4
5
0
Order By: Relevance
“…No significant change was detected in Ficoll clearance over the radius range (30 to 48 Å in this study) nor was there a change in GFR. This is consistent with previous overload studies showing the lack of change in the glomerular size selectivity (1) or a change too modest to account for a marked increase in albumin excretion (23). These results suggest that changes in the glomerular size selectivity are not responsible for the changes in albumin excretion in this model.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…No significant change was detected in Ficoll clearance over the radius range (30 to 48 Å in this study) nor was there a change in GFR. This is consistent with previous overload studies showing the lack of change in the glomerular size selectivity (1) or a change too modest to account for a marked increase in albumin excretion (23). These results suggest that changes in the glomerular size selectivity are not responsible for the changes in albumin excretion in this model.…”
Section: Discussionsupporting
confidence: 92%
“…The absolute levels of protein excretion are also similar to those seen in glomerulonephritis in Sprague-Dawley rats, with excretion rate of 2-3 mg/day/kg body wt (18), and those in the isolated perfused rat kidney when perfused with 50 mg/mL BSA (28). The reversibility of proteinuria shown here is consistent with other studies (1,35). Large coefficient of variation in the levels of protein excretion reflects, in part, high variability in the levels of plasma protein concentration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several studies have utilized albumin overload models in mice, rats, and cultured cells and distinct differences between rat strains have been demonstrated. 9,10,21,23 The question of whether persistent proteinuria can be detrimental to kidney function remains controversial. 24 Several studies have documented glomerular structural changes including podocyte flattening and foot process fusion, 9,25,26 however normal glomeruli were also observed in these same studies.…”
Section: Discussionmentioning
confidence: 99%
“…28 Although there are reports suggesting that in healthy individuals dietary protein overload may not increase protein renal clearance, 29,30 animal models showed that protein overload increases proteinuria. 31,32 In humans also it was shown that consumption of excessive amounts of dietary protein promotes chronic renal disease through increased glomerular pressure and hyperfiltration 33 and might be harmful in patients with CKD. 34 Therefore, dietary differences in the amount of protein consumption may result in differences in GFR and albumin clearance and the amount of albumin measured in a urine sample.…”
Section: Microalbuminuria: Is What Is Measuredmentioning
confidence: 99%